Lessons learned from study of WWII Veterans with Dementia - Hanna Ulatowska (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
In our six-year study, Dr. Ulatowska and her coworkers collected the testimonial language of eighty WWII veterans who volunteered to participate in semi-structured interviews about their wartime experiences. The veterans of WWII have a unique shared group of identities and values that are characteristic of this period in American culture which is well documented in the literature [1].